Moderating Role of Transformational Leadership between Strategic Lenses and Organizational Innovation in the Jordanian Telecommunication Companies - Al-Zu’bi, Hasan Ali; Alzghoul, Amro; Awamleh, Fawwaz Tawfiq (International Review of Management and Marketing, 2025)
This research study focuses on the interplay of strategic lenses with transformational leadership and organizational innovation in Jordanian telecommunication companies. Strategic orientation, hence enabled by the application of strategic lenses, becomes very important within the dynamic environment of the telecommunications industry to respond to market complexities and innovation. The strategic lenses provide a multilateral frame for understanding and appraising organizational strategies through the importance of holistic strategy making. Although strategic lenses significantly influence organizational innovation, this study suggests that transformational leadership could play a moderating role. Transformational leadership based on inspirational motivation, intellectual stimulation, and individual consideration adds value to the relationship between strategic orientations and innovation outcomes. This study will use a quantitative research approach and target the management staff at the top and middle levels of employees from various Jordanian telecommunication companies to assess the moderating effect of transformational leadership in the strategic lens-organizational innovation nexus. The results show that while the role of transformational leadership is to moderate the translation of strategic insights into innovative practices, it further strengthens the impact of strategic orientations on organizational innovation. Thus, this study makes its contribution to the existing literature through an emphasis on the synergistic effect of strategic lenses and transformational leadership on the fostering of organizational innovation. It, therefore, means that scholars and practitioners will find valuable insights targeting the enhancement of innovation capability within the telecommunications sector.